Wireless personal area networks : - Misic, Jelena (John Wiley & Sons, Ltd., 2007)
This compact but comprehensive analysis demystifies the new standards for low data rate personal area networks (LR-WPANs), including related standards on Bluetooth. Misic and Misic (both U. of Manitoba) describe how the standards relate to the operation of wireless personal area networks (WPANs), single-cluster networks, including clusters with uplink traffic, clusters with uplink and downlink traffic, medium access control layer performance limitations, activity management through Bernoulli scheduling, and admission control issues. They analyze multi-cluster networks, including cluster interconnections with master-slave bridges, equalization of cluster lifetimes, and cluster interconnects with slave-slave bridges, and security, including the cost of secure and reliable sensing. With summaries, lists of further reading, and a wealth of practical examples, this serves well as a course text for graduate students and as a professional reference.